Private Participation in the Airport Sector : Recent Trends - Silva, Gisele F. (World Bank, Washington, DC, 2012)
During the 1990s private sponsors have participated in projects involving eighty-nine airports in twenty-three developing countries, with investment totaling US$5.4 billion. About three-fifths of this investment was carried out in 1998 alone, and about two-fifths related to the award of the Argentine airport system that year. Analysis of the investment patterns shows that Latin America leads in attracting private investors, operations and management contracts with major capital expenditure have been the main vehicle for investment, and governments are transferring networks to the private sector more often than single airports or stand-alone facilities.